Does Bank Size Matters? A Pre and Post-Merger Productivity Analysis in Malaysian Financial Institutions using DEA and Malmquist Index - Hazlina, Abd Kadir; Muzafar Shah, Habibullah (INTI International University, 2018)
The aim of this study is to investigate the productivity growth amongst the local commercial banks in Malaysia before and after 1999 mega bank merger. In this context, we attempt to evaluate the technical efficiency, efficiency change, technical change and productivity of finance companies using the Malmquist index approach and the Data Envelopment Analysis amongst the local commercial banks in Malaysia from 1990 to 2005. In this context, the study will highlight the performance of local commercial banks before and after the merger process.